Analisa konflik: sektor kehutanan di Indonesia 1997-2003 - Wulan, Y.C.; Yasmi, Yurdi; Purba, C.; Wollenberg, Eva Karoline (Center for International Forestry Research, 2004)
This paper provides a profile of forest-related conflict in Indonesia 1997 to June 2003, based on a survey of national and provincial newspaper articles and six case studies in Sumatera, Kalimantan and Java. The report shows that conflict increased most rapidly in 2000 during the transition to decentralization, and has generally stayed at higher levels than during the New Order period. Reports of conflicts were highest in East Kalimantan, followed by Sumatera and Central Java. The causes of conflict were primarily differences in perceptions about boundaries, rights to use of forest, compensation payments and distribution of benefits from forests. Although media reports focus on the escalation of conflict after the reform period, the case studies demonstrated complex histories of latent conflict and conflict resolution through compensation payments that proved unsuccessful in reducing long-run conflict. The study recommends that (i) conflict management be considered an element of forest management, (ii) forest conflicts should be monitored to learn more about their incidence, causes and ways of managing them and (iii) alternative methods for managing conflict should be explored.